Anemia and Transfusion in Infective Endocarditis - Tim Alberts; Susanne Eberl; Thomas W. van der Vaart; S. Matthijs Boekholdt; Henning Hermanns (Reviews in Cardiovascular Medicine, 2025)
Infective endocarditis (IE) is a severe condition characterized by a predominantly bacterial infection of the heart valves or endocardial surface, often leading to significant morbidity and mortality. Anemia is very common in patients with IE, which may be explained by factors such as chronic inflammation, hemolysis, kidney disease, and pre-existing iron deficiency. This review aimed to comprehensively examine the prevalence, causes, and clinical impact of anemia in IE patients and the role of blood transfusion in managing these patients. The diagnostic approach to anemia in IE includes combining clinical assessment and laboratory investigations, specifically distinguishing between different etiologies. Blood transfusion is likewise very common in IE, especially in surgically treated patients. Thus, balancing the need to correct anemia with the risks associated with blood transfusion is complex, and robust evidence is scarce. Management strategies for anemia in IE may extend beyond transfusion, encompassing pharmacological treatments such as iron supplementation and erythropoiesis-stimulating agents. Despite advancements in understanding the interplay between anemia and IE, several knowledge gaps and unresolved questions remain, necessitating further research to refine treatment protocols and improve patient outcomes. Future directions include investigating emerging therapeutic approaches, optimizing multidisciplinary care pathways, and developing evidence-based guidelines tailored to the unique needs of IE patients. This review underscores the importance of a comprehensive, individualized approach to managing anemia and transfusion in IE, aiming to enhance clinical outcomes and quality of life for affected patients.